2016
DOI: 10.1007/978-3-319-38968-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Research in Statistics Education

Abstract: In this ICME-13 Topical Survey, we provide a review of recent research into statistics education. We focus our review on empirical research that has been published in established educational journals or the proceedings of important conferences that include at least a section referring to statistics education. We have identified and will address six important research topics, namely, teacher knowledge, teachers' statistics-related affect, teacher preparation, student knowledge, students' statistics-related affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 99 publications
0
7
0
3
Order By: Relevance
“…However, while a project-based course usually implies an active learning course, with just 20% of the course assessment focused on active learning, it could be that the two formats are similar and more akin to traditional pedagogy. Accordingly, these less-favorable reports (Ramirez and Bond 2014) could be supporting the notion that students who pursue an introductory statistics course based on traditional pedagogy are less likely to appreciate the value of statistics, and hence those students are less inclined to consider taking another statistics course. Indeed, the results from the wider published literature are quite varied in this regard, and, in some instances, counterintuitive, which could be attributed to inconsistency in instrumentation across studies and curricular design, particularly regarding what constitutes the core elements of an active learning introductory statistics course (Carlson and Winquist 2011).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, while a project-based course usually implies an active learning course, with just 20% of the course assessment focused on active learning, it could be that the two formats are similar and more akin to traditional pedagogy. Accordingly, these less-favorable reports (Ramirez and Bond 2014) could be supporting the notion that students who pursue an introductory statistics course based on traditional pedagogy are less likely to appreciate the value of statistics, and hence those students are less inclined to consider taking another statistics course. Indeed, the results from the wider published literature are quite varied in this regard, and, in some instances, counterintuitive, which could be attributed to inconsistency in instrumentation across studies and curricular design, particularly regarding what constitutes the core elements of an active learning introductory statistics course (Carlson and Winquist 2011).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have noted considerably lower levels of perceived usefulness or value. For example, Ramirez and Bond (2014) reported that only 20% of students (35 out of 175) who completed an introductory statistics course were neutral or expressed some degree of usefulness for the course. One plausible explanation for these mixed reports is the lack of consistency in how attitude and its components (including perceived usefulness) are measured and interpreted; this factor could limit comparability across studies (Nolan, Beran, and Hecker 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental results are handled by mathematical statistical methods [9], [10] as follows: (i) Make a table of distribution of frequencies, cumulative frequency; (ii) Graph the cumulative line from the cumulative frequency distribution table; (iii) Calculate the typical parameters.…”
Section: Resultsmentioning
confidence: 99%